On the Merits of the Ethnographic Method in Economic Research: A Zambian Illustration - Seshamani, Venkatesh (Archives of Business Research, 2019)
In view of the growing recognition of the limitations of quantitative methods of economic research, there is a noticeable revival of the application of qualitative methods. This paper discusses one such qualitative method, the ethnographic method, which is growing in popularity. An illustration is provided in the Zambian context, using ethnographic techniques to understand the present Zambian money mobile system from the perspectives of the different players, namely, sneders and recipients of mobile money, mobile money service providers and individual mobile money agents.